Thermal imaging to phenotype traditional maize landraces for drought tolerance - Costa, Joaquim Miguel; Tejero, Ivan Francisco Garcia; Zuazo, Victor Hugo Duran; Lima, Roberta Samara Nunes da; Chaves, Maria Manuela; Vaz Patto, Maria Carlota (Comunicata Scientiae, 2015)
Searching and identification of new crops or varieties with higher adaptation or resistance to water stress is one of the strategies to make agriculture profitable and more sustainable. Especially en arid and semi areas with limiting water resources. This study establishes a practical, fast and replicable protocol to select maize genotypes for its capability to respond to water stress. Eight Portuguese maize landraces (LD), traditionally grown in areas with different altitude and subjected to potentially different degrees of water stress (low altitude = potentially lower stress; high altitude = potentially higher stress) was used. Seedlings were subjected to continuous watering (FI) or forced to water withholding (non-irrigated) for a period of 7-8 days followed by re-watering (NI). Leaf temperature was determined every 48 h by thermal imaging and the temperature difference between NI and FI plants (ΔTNI-FI) was calculated. We found that those genotypes that traditionally had been grown at higher altitudes kept more stable leaf temperature values under dry or wet conditions (small ΔTNI-FI) even under severe water stress. These results will help to optimize a screening protocol for maize seedlings and select novel genotypes or LDs better adapted to water stress, especially in regions where irrigation water is scarce.